(untitled) (London Journal of Research In Management & Business, 2025)
The goal of this monograph is to measure the impact of minimum wage (MW) on income distribution between 2012 and 2018, whether positive or negative, following the steps adopted by Brito (2015) in chapter III, where the author analyzed the impact of MW on income distribution between 1995 and 2011. For this analysis, we performed the standard Blinder- Oaxaca decomposition method (mean) and the method proposed by FFL (2009), where we can use the Blinder-Oaxaca decomposition for other statistics besides mean (such as Gini index, percentiles and interquantile differences), based on the microdata of the Continuous National Sample Survey by Domicile (PNAD Contnua) of the years 2012, 2014, 2016 and 2018 conducted by the Brazilian Institute of Geography and Statistics (IBGE), which allows us to analyze the impact of different minimum wage strips on each statistic of our interest for different periods. The decomposition made by these two methodologies allows us to observe the inequality of income caused by the differences in characteristics of the two groups analyzed, in our case, pairs of years (2012-2018, for example). The results of this work show us that the minimum wage generally contributed to reduce inequality between 2012 and 2014, and especially between 2016 and 2018, but between 2014 and 2016, the minimum wage contributed to increase inequality. This contribution to increasing inequality between 2014 and 2016 can be explained by the reduction of income in the lower tail of the distribution plus the increase of income in the upper tail. As for the whole period between 2012 and 2018, both the direct effect of the minimum wage (captured by the strip from 0.9 to 1.1 MW) and the expanded effect (from 0.5 to 1.5 MW), which considers possible spillovers and cash effects, contributed to increasing inequality of income in Brazil.